MACROECONOMIC VOLATILITY, SECURITY ALLOCATIONS, AND MATERNAL MORTALITY IN NIGERIA: A VECTOR ERROR CORRECTION APPROACH - Sophia Maimuna John (International Journal on Economics, Finance and Sustainable Development, 2026)
The intersection of fiscal reallocations driven by internal security threats and open-economy monetary shocks presents a profound policy challenge for resource-dependent developing nations. While traditional public health literature focuses heavily on clinical or micro-level institutional determinants of maternal death, it frequently overlooks the macro-fiscal and monetary transmission channels that dictate real health-resource efficacy. This study empirically investigates the extent to which exchange rate depreciation mediates or exacerbates the relationship between military expenditure and maternal mortality in Nigeria. Utilizing annual time-series data spanning from 2000 to 2024, the study employs a rigorous Vector Error Correction Model (VECM) under the Johansen cointegration framework to separate long-run structural equilibria from short-run dynamic innovations among uniformly integrated I (1) series. The long-run normalized structural equation reveals a stark dual-threat mechanism affecting maternal health. First, military expenditure exhibits a statistically significant positive elasticity (β= 0.245), validating the Samuelsonian "Guns versus Butter" hypothesis where rising security funding systematically crowds out nominal social budgets. Second, exchange rate depreciation exerts a significant positive effect on the maternal mortality ratio (β= 0.188), confirming an intense import-dependence pass-through mechanism. Because Nigeria relies on imports for over 70% of its medical inputs, currency devaluation functions as a severe cost-push supply shock that prices vulnerable demographics out of obstetric care. The Error Correction Term (ECTt-1 = -0.385) indicates that while the system maintains long-run stability, short-run shocks to defense and currency values take approximately 2.6 years to resolve, leaving pregnant populations highly exposed in the interim. To mitigate these macro-structural hazards, Nigeria must establish ring-fenced fiscal buffers for maternal healthcare that are legally insulated from defense reallocations. Additionally, policymakers should deploy targeted counter-cyclical foreign exchange subsidies for essential medical imports and aggressively incentivize vertically integrated domestic pharmaceutical manufacturing to decouple human capital survival from external monetary volatility.